Factors related to attitudes toward diversity in Australia, Malaysia, and Puerto Rico - Brown, Jac; Jiménez, Aida L; Sabanathan, Dharshika; Ssekamanya, Siraje Abdallah; Hough, Michael; Sutton, Jeanna; Rodríguez, Jose; García Coll, Cynthia (Taylor & Francis Group, 2018)
In this study, we tested social identity complexity theory (Roccas & Brewer, 2002) in relation to attitudes toward diversity and the associated variables of patriotism, nationalism, religiosity, aggression, and sense of self (well-being) in a cross-cultural study of 398 Malaysian, 239 Australian, and 201 Puerto Rican students. Puerto Ricans reported the most positive attitudes toward diversity, followed by Australians, and finally Malaysians. For Puerto Ricans, pro-diversity attitudes were predicted by a positive correlation with constructive patriotism and a negative correlation with blind patriotism. For Australians, pro-diversity attitudes were predicted by a positive association with constructive patriotism, a negative association with traditional nationalism, and a negative association with physical aggression. For Malaysians, pro-diversity attitudes were predicted by positive relationships with all of the following variables: constructive patriotism, traditional nationalism, verbal aggression, hostility, and the need to bolster self through idealizing others. These results support social identity complexity theory and partially support associated predictions for Australians, Puerto Ricans, and some of the predictions for Malaysians. The results are explained in terms of local cultural contexts that may not easily be understood by a simple understanding of the variables that were measured.